'Ammonia, lactate and blood gases – A user's guide'. Issue 3 (March 2019) - Davison, James E.
Abstract: Basic biochemical tests are frequently obtained in acutely unwell neonates and children, as well as in some elective situations. Correct interpretation can be invaluable in identifying rare inherited primary metabolic disorders, but secondary causes of hyperammonaemia, elevated blood lactate or blood gas derangement are more common and require appropriate treatment of the underlying cause. This Personal Practice guide provides an overview of these tests and their interpretation.